Health education of parents mental health : Pendidikan Kesehatan Orangtua tentang Covid-19 terhadap Kesehatan Mental Remaja - sri hartati; Lutiyah Lutiyah; Tantan Hadiansyah (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2022)
Health education is a dynamic process of behavior change where the changes that occur are not just the process of transferring material from one person to another and not a set of procedures, but these changes occur because of awareness from within the individual, group, or society itself. Public health emergencies, such as pandemics, have an impact on both physical and mental health. Children are especially vulnerable because of their limited understanding of the event. They cannot escape the dangers of situations physically and mentally because they have limited coping strategies. They may not be able to communicate their feelings like adults. Closing schools and separation from friends can cause stress and anxiety in children. Exposure to mass media coverage of crisis events and unverified information circulating on social media can exacerbate mental stress. This study aims to determine the effect of parental health education about Covid-19 on the mental health of adolescents at SMK Dharma Kusuma Cianjur. The research method used is one group pre test and post test design. This research was conducted from January 03 to January 29, 2022. Respondents were parents and teenagers in class X totaling 196 people. Data collection was carried out by observing, analyzing data using the Kendall's tau test, comparing research before and after the intervention was given. There are differences in adolescent mental health before and after parents are given health education (0.013 <0.05). Teenagers and parents should establish a warm and harmonious relationship, open and trust each other so that mental health problems do not occur.